2019
DOI: 10.1017/s0031182019001744
|View full text |Cite
|
Sign up to set email alerts
|

CD14+monocytes are the main leucocytic sources of CXCL10 in response toPlasmodium falciparum

Abstract: The CXCR3 chemokine CXCL10 or IFN-γ inducible protein 10 (IP-10) has been identified as an important biomarker of cerebral malaria (CM) mortality in children. Studies in mouse malaria infection models have shown that CXCL10 blockade alleviates brain intravascular inflammation and protects infected mice from CM. Despite the key role that CXCL10 plays in the development of CM, the leucocytic sources of CXCL10 in response to human malaria are not known. Here we investigated CXCL10 responses to Plasmodium falcipar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…However, when the disease's circumstances become complicated and severe (as in CM), higher CXCL10 levels are detected in the blood circulation of patients [4][5][6] . Of note, although it appears that monocytes are one of the main sources of production of CXCL10 in response to P. falciparum infection 64 , this chemokine is released also by other cells such as neutrophils, eosinophils, and dendritic cells [65][66][67] . If and how the parasite communicates with these other host cells to alter CXCL10 production remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the disease's circumstances become complicated and severe (as in CM), higher CXCL10 levels are detected in the blood circulation of patients [4][5][6] . Of note, although it appears that monocytes are one of the main sources of production of CXCL10 in response to P. falciparum infection 64 , this chemokine is released also by other cells such as neutrophils, eosinophils, and dendritic cells [65][66][67] . If and how the parasite communicates with these other host cells to alter CXCL10 production remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…To further corroborate the pathological role of CXCL-10 in malaria, elevated levels of this molecule were associated with increased risk of fatal cerebral malaria in children [ 68 ]. In a recent study, CD14 + monocytes were identified as the main producers of CXCL-10 when challenged with P. falciparum , but the sub-sets that were involved and the association between CXCL-10 levels and parasite burden in humans remain unknown [ 69 ]. In addition, using an in vitro model of human blood monocyte-derived microglia cells, the uptake of IE-derived extracellular vesicles was shown to cause down-regulation of IL-6 and IL-10 gene expression [ 70 ].…”
Section: Heterogeneity In Host Phagocyte Subpopulations: Who Is the Big Eater?mentioning
confidence: 99%
“…IP-10 is also known to be a pro-tumorigenic chemokine that has been strongly correlated with the progression of breast cancer given that it is more largely secreted by the malignant than non-malignant tissues [ 14 ]. IP-10 is produced by multiple cell types, such as activated monocytes, macrophages, neutrophils, DCs, pre-adipocytes/adipocytes, hepatocytes, astrocytes, endothelial cells, keratinocytes, fibroblasts, mesenchymal cells, and pancreatic β cells [ 9 , 15 , 16 , 17 ] as well as by breast tumor cells, per se [ 18 ]. IP-10 expression is induced by lipopolysaccharide and proinflammatory cytokines, including IL-1 and tumor necrosis factor-α (TNFα) [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%